Transformasi Pendidikan Akuntansi melalui Platform E-Learning Peran LMS dalam Meningkatkan Efektivitas Belajar Mahasiswa - Amelia, Putri; Suranto, Suranto (Cetta: Jurnal Ilmu Pendidikan, 2025)
The transformation of education in the digital era has become an urgent necessity to meet the demands of an increasingly connected modern society. Higher education institutions need to integrate digital technology into the learning process to enhance the quality of education. This research aims to examine the utilization of e-learning platforms based on Learning Management Systems (LMS) in improving the effectiveness of learning for accounting education students at Universitas Muhammadiyah Surakarta. A qualitative approach was employed in this study, with data collected through semi-structured interviews with two lecturers and five students, as well as direct observation. The research utilized triangulation techniques, including data source triangulation and method triangulation. This study delved into the experiences of lecturers and students regarding the implementation of LMS. The findings indicate that LMS provides various significant benefits, such as ease of accessing learning materials flexibly, more systematic assignment management, and increased motivation and learning effectiveness among students. LMS also encourages independent learning and facilitates active interaction between students and lecturers. However, there are several challenges in the implementation of LMS, including technical disruptions such as server issues, the unavailability of mobile-based applications, limited understanding of the features of LMS by lecturers and students, and restricted support for additional features, such as Turnitin, to address plagiarism. The study concludes that LMS has great potential to enhance the effectiveness of learning for accounting education students, despite the challenges that need to be addressed. More intensive efforts are required to overcome technical barriers for both lecturers and students, improve users' understanding of the features of LMS, and develop supporting features to ensure that the utilization of LMS in the learning process can be more optimal. The results of this research are expected to serve as a reference in developing strategies for digital-based educational transformation.